MACROECONOMIC STABILITY ON ISLAMIC ECONOMIC PERSPECTIVE: TOWARDS EQUITABLE AND SUSTAINABLE ECONOMIC GROWTH - Risdiana Himmati; Citra Mulya Sari; Lativa Hartiningtyas; Rendra Erdkhadifa (UIN Raden Mas Said Surakarta, 2024)
This study aims to determine macroeconomic stability in the perspective of Islamic economics towards equitable and sustainable economic growth. In this context, Islamic economics emphasizes justice, equal distribution of income, and prevention of practice usury. Policy government such using of zakat and policy in appropriate monetary with Islamic principles can help reach stability of economics. The method in this study uses literature study approach. The main purpose to reach in this study is significantly important for evaluating economics policy related to growth fair economy. The analysis shows that from perspective Islamic economics, stability macroeconomics will be evaluated and improved by policy supporting economics investment, equal distribution of income, and growth of sustainable economy.